The Relationship between Finger Muscle Strength and Hand Eye Coordination on Volleyball Passing Results in Extracurricular Participants Ma Ppth Tembilahan - supriadi supriadi; devit wilastra (FKIP Universitas Islam Indragiri, 2023)
This study aims to determine the relationship between finger muscle strength and hand eye coordination on the results of passing in volleyball. The method in this research is correlation with descriptive research type. The number of research samples is 9 students with purposive sampling method. Measurement of finger muscle strength using a Handgrip Dynamometer. Hand eye coordination was measured by throwing and catching the ball test. Measurement of passing over by bouncing the ball against the target wall. The results of this study indicate that there is a significant relationship between finger muscle strength and the results of passing volleyball rcount = 0.984 > rtable = 0.666. and there is a significant relationship of hand eye coordination to the results of passing on volleyball rcount = 0.91 > rtable = 0.666. and there is also a significant relationship between finger muscle strength and hand-eye coordination on the results of passing volleyball Rcount = 0.872 > Rtable = 0.666. then the relationship between variable (X1) variable (X2) and variable (Y) can be calculated. The truth is tested using the F-test and Fcount = 9.77 > Ftable = 5.14. from the results of these calculations it can be concluded that there is a significant relationship between (X1X2Y ) the extracurricular participants of MA PPTH Tembilahan students.